Emerging photonic devices based on photonic liquid crystal fibers - Wolinski, Tomasz R.; Ertman, Slawomir; Budaszewski, Daniel; Chychlowski, Milosz; Czapla, Aleksandra; Dabrowski, Roman; Domański, Andrzej W.; Mergo, Pawel; Nowinowski-Kruszelnicki, Edward; Rutkowska, Katarzyna; et al. (Photonics Letters of Poland, 2011)
Photonic liquid crystal fibers (PLCFs) define a new class of optical waveguides that combines unique properties of microstructured photonic crystal fibers and liquid crystals. Current progress of research in the field of PLCFs means that a new class of emerging photonics devices can be expected, i.e. tunable attenuators, tunable broad-band filters, tunable polarizers (with an arbitrary PDL and a variable axis of polarization), tunable waveplates, and tunable phase shifters with high retardance will appear in the near future. In this work we would like to discuss this perspective, paying special attention to two most challenging technological issues such as control of LC molecules orientation and permanent connecting of PLCFs to standard fibers. Full text: PDF References: P.J. Russell, "Photonic-Crystal Fibers", J. Lightwave Technol. 24, 4729 (2006). [CrossRef] D.B. Eggleton et al, "Microstructured optical fiber devices", Opt. Exp. 9, 698 (2001). [CrossRef] T.T. Larsen et al., "Optical devices based on liquid crystal photonic bandgap fibres", Opt. Exp. 11, 2589 (2003). [CrossRef] T.R. Woliński et al, "Propagation properties of photonic crystal fibers filled with nematic liquid crystals", Opto-Electronics Rev. 13(2), 177 (2005). [DirectLink] J. Du et al., "Liquid crystal photonic bandgap fiber: different bandgap transmissions at different temperature ranges", Appl. Opt. 47, 5321 (2008). [CrossRef] M.Y. Jeon, J.H. Kim, "Transmission Characteristics in Liquid-Crystal-Infiltrated Photonic Crystal Fibers", Japan. Jour. Appl. Phys. 47(4), 2174 (2008). [CrossRef] Q. Lu, S.T.Wu, "Electrically tunable liquid-crystal photonic crystal fiber", Appl. Phys. Lett. 85, 2181 (2004). [CrossRef] M.W. Haakestad et al., "Electrically tunable photonic bandgap guidance in a liquid-crystal-filled photonic crystal fiber", IEEE Photon. Technol. Lett. 17, 819 (2005). [CrossRef] T.R. Wolinski et al., "Influence of temperature and electrical fields on propagation properties of photonic liquid-crystal fibres", Meas. Sci. Technol. 17, 985 (2006). [CrossRef] L. Scolari et al., "Continuously tunable devices based on electrical control of dual-frequency liquid crystal filled photonic bandgap fibers", Opt. Expr. 13, 7483 (2005). [CrossRef] A. Lorenz et al., "Photonic crystal fiber with a dual-frequency addressable liquid crystal: behavior in the visible wavelength range", Opt. Expr. 16, 19375 (2008). [CrossRef] T. Alkeskjold et al., "All-optical modulation in dye-doped nematic liquid crystal photonic bandgap fibers", Opt. Expr. 12, 5857 (2004). [CrossRef] V.K. Hsiao, C.-Y. Ko, "Light-controllable photoresponsive liquid-crystal photonic crystal fiber", Opt. Expr. 16, 12670 (2008). [CrossRef] L. Scolari et al., "Frequency tunability of solid-core photonic crystal fibers filled with nanoparticle-doped liquid crystals", Opt. Expr. 17, 3754 (2009). [CrossRef] T.T. Alkeskjold, A. Bjarklev, "Electrically controlled broadband liquid crystal photonic bandgap fiber polarimeter", Opt. Lett. 32, 1707 (2007). [CrossRef] T.R. Wolinski et al., "Polarization effects in photonic liquid crystal fibers ", Meas. Sci. Technol. 18, 3061 (2007). [CrossRef] T.R. Woliński et al., "Tunable highly birefringent solid-core photonic liquid crystal fibers", Opt. Quantum Electron. 39(12-13), 1021 (2007). [CrossRef] S. Ertman et al., "Light propagation in highly birefringent photonic liquid crystal fibers ", Opto-Electronics Review 17, 150 (2009). [CrossRef] L. Wei et al., "Continuously tunable all-in-fiber devices based on thermal and electrical control of negative dielectric anisotropy liquid crystal photonic bandgap fibers", Appl. Opt. 48, 497 (2009). [CrossRef] S. Ertman et al., "Low-loss propagation and continuously tunable birefringence in high-index photonic crystal fibers filled with nematic liquid crystals", Opt. Expr. 17, 19298 (2009). [CrossRef] T.R. Woliński et al., 2010 International Conference on Photonics, ICP2010, art. no. 5604369. T.R. Woliński et al., "Liquid crystal photonic crystal fibers and their applications", Proc. SPIE 7955, 795502 (2011). [CrossRef] V.V. Presnyakov et al, "Infiltration of photonic crystal fiber with liquid crystals", Proc. SPIE 6017, 60170J-1-7 (2005). [CrossRef] S. Ertman et al, "Liquid crystal molecular orientation in photonic liquid crystal fibers with photopolymer layers ", Proc. SPIE 6587, 658706 (2007). [CrossRef] M.S. Chychłowski et al., "Photo-Induced Orientation of Nematic Liquid Crystals in Microcapillaries", Acta Phys. Polonica A 118, 1100 (2010). [DirectLink] M. Murawski et al., "A photonic crystal fiber splice with a standard single mode fiber", Phot. Lett. Poland 1(3) 115 (2009).[CrossRef]